A Distributed Normalized Explicit Preconditioned Conjugate Gradient Method - Gravvanis, G.A.; Giannoutakis, K.M.; Missirlis †, N.M. (Parallel algorithms and applications, 2004)
A new parallel normalized explicit preconditioned conjugate gradient method in conjunction with normalized approximate inverse matrix techniques is presented for solving efficiently sparse linear systems on multi-computer systems. Application of the proposed method on a three dimensional boundary value problem is discussed and numerical results are given. The implementation and performance on a distributed, memory MIMD machine, using message passing interface (MPI) is also investigated. E-mail: nmis@di.uoa.gr